2017
DOI: 10.4103/psychiatry.indianjpsychiatry_368_16
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of intention to quit tobacco among construction site workers in Delhi, India

Abstract: Background:Information on predictors of quitting behavior among construction site tobacco users is scarce in India. Hence, this study was conducted to assess the intention of tobacco users toward quitting and its predictors with reference to sociodemographic profile.Methodology:A community-based, observational study was conducted on adult 172 construction site workers in a university campus of Delhi. Data were collected by an interview using the WHO-adopted, pretested, semi-structured questionnaire. Chi-square… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…The present study found that adequate knowledge of smoking-related illnesses was absent in 27% of participants, much higher than the 5% reported by GATS-2. Previous studies have reported that an increase in knowledge about tobacco risks and harmful effects can increase the quit attempt rates in smokers 16 . Furthermore, healthy smokers are often unaware of smoking cessation services, even in developed nations 17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study found that adequate knowledge of smoking-related illnesses was absent in 27% of participants, much higher than the 5% reported by GATS-2. Previous studies have reported that an increase in knowledge about tobacco risks and harmful effects can increase the quit attempt rates in smokers 16 . Furthermore, healthy smokers are often unaware of smoking cessation services, even in developed nations 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that an increase in knowledge about tobacco risks and harmful effects can increase the quit attempt rates in smokers 16 . Furthermore, healthy smokers are often unaware of smoking cessation services, even in developed nations 17 .…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] Only 24.6% migrant construction site workers expressed an intention to quit in a year compared to 73% (56.5% smokers and 81% SLT users) in Delhi and 46% in Mysore. [ 42 43 ]…”
Section: Discussionmentioning
confidence: 99%
“…study intending to quit were literate (75.0%), started tobacco use >15 years of age (75.4%), occasional tobacco users (78.9%), and less dependent on nicotine (74.4%). [ 42 ] In West Bengal, Islam et al . identified age above 40 years, illiteracy, initiation of tobacco use between 11 and 15 years of age, daily tobacco users, duration of use above 20 years, and high self-reported nicotine dependency as characteristics associated with no intention of quitting tobacco and SLT users were associated with an odds ratio (OR) of 2.05 for “setting a quit date“ when compared to smokers.…”
Section: Discussionmentioning
confidence: 99%
“…However, a handful of studies conducted among specific populations like the rural population of Dehradun, urban slum dwellers of West Bengal, and construction workers reported willingness to quit ranging between 54% and 73% among the tobacco users. [ 22 23 24 ]…”
Section: Discussionmentioning
confidence: 99%